التوظيف الإعلامي للأحزاب السياسية ودوره في تعزيز الوعي بالقضية الفلسطينية لدى طلبة الجامعا ت دراسة مقارنة بين حركة الشبيبة والكتلة الإسلامية - أمجد محمد الجلاد
This thesis is the first of its kind, as it discusses the media employment practised by the Youth Movement and the Islamic Bloc, to discover its role in enhancing university students' awareness of the Palestinian issue. The thesis aims to reveal the reality of the political size of each of the Student Youth Movement and the Islamic Bloc in An-Najah and Kadoorie Universities, the nature of political propaganda that they practice on students, and its repercussions on the degree of their affiliation and national identity, to create a model that defines the characteristics of partisan media in Palestine. This study relied upon pairing the quantitative and qualitative approaches in its tools to answer the study questions. In the quantitative approach, the questionnaire was relied upon as the main tool, and it was distributed in a stratified random manner to (380 male and female students) from the study population, which consisted of about 34,000 male and female students, while the qualitative approach was used to analyze the questions of 6 interviews, which were conducted on a number of workers and officials in the student movement and some media experts in Palestinian affairs. The study also used data, books, periodicals and publications related to the role of Palestinian political parties in developing political awareness among university students. The study came out with a set of results, the most prominent of which was that 87% of the students in the study sample believe that partisan media disputes negatively affect the unity of the Palestinian, while 85% of them believe that partisan dependence on the media has affected its media policy. 80% of them believe that the party media cares about the party’s opinion and serves its goals at the expense of national interests, which frames the fact that political parties depend mainly on prioritizing in their handling of events, and harnessing them to serve their agenda. While 80% of the study sample see that the political differences between the Palestinian parties are reflected in the interest of the homeland, which establishes the importance of turning around to adopt a responsible party discourse that has the spirit of dialogue and national pluralism and works to end the Palestinian division through a unified national media plan, and the establishment of a Palestinian media system capable of responding to the requirements of the Israeli-Palestinian conflict, and the need to move the Palestinian partisan media from the local level to the global through the establishment of media channels that support the Palestinian issue and expose the practices of the Israeli occupation, and the need for those in charge of the party media to take into account the privacy of Palestinian society and work to dissolve differences and mobilize all energies in the service of the Palestinian issue.